Perkembangan Teori Karier Dan Relevansinya Dengan Pendidikan Kejuruan - Kusuma, Hanif Aulia; Tuwoso, Tuwoso; Marsono, Marsono (BRILIANT: Jurnal Riset dan Konseptual, 2025)
Vocational education is a level of education that is the focus of development in Indonesia's 2045 vision. In 2045, it is predicted that 90% of workers will be dominated by the workforce from high school and university level. The aim of writing this article is to examine career development theories relevant to vocational education. The career theory relevant to vocational education is SCCT. The theory used in developing SCCT is a theory with the P-E Fit paradigm and Developmental Theory. One of the theories with the P-E Fit paradigm is the theory coined by Holland, namely RIASEC. This theory determines individual character based on 6 elements that are appropriate to the world of work. The next theory is Ginzberg's Developmental Theory. According to Ginzberg, career development is plotted into 3 age categories. SCCT is a development of previous theories (P-E Fit and Developmental Theory). Based on the previous discussion, RIASEC theory tends to discuss vocational interests, of which interest is one model of SCCT. Meanwhile, based on Developmental Theory Ginzberg has a position as a predictor of learning experience in the SCCT model.